Allah speaks to the prophet musa: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story recounts the profound moment when Allah communicates directly with Prophet Musa at the burning bush. It highlights the importance of obedience, faith, and the divine mission given to Musa to lead his people out of oppression. The story emphasizes the significance of listening to God's guidance and the courage needed to fulfill one's purpose.